Determinants of Income from Rabbit Production in Lagos State, Nigeria - Aminu, F.O.; Fasugba, O.M.; Ogoloyinbo, O.D. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
The study examined the determinants of income from rabbit production in Lagos State, Nigeria. It specifically estimated the profitability of rabbit production, analysed the determinants of income from rabbit production and identified the constraints to rabbit production in the study area. A two stage sampling techniques was used to select 40 rabbit farmers from Epe and Ikorodu Local Government Areas and data was collected with the aid of questionnaire. Data were analysed using descriptive statistics, budgetary analysis and multiple regression analysis. Results revealed that the rabbit farmers were young with a mean age of 37 years, educated (100%), married (62.5%) with a mean stock size of 35 rabbits. Result from the budgetary analysis revealed that, the average total cost incurred by the rabbit farmers per production cycle was ₦91,546.19 while total revenue of ₦121,950 was realized thereby returning a net farm income of ₦30,403.81. The benefit cost ratio was ₦1.33. Educational level of respondents (p<0.01), marital status (p<0.01), rabbit production experience (p<0.10) and Stock size (p<0.01) were the factors determining income from rabbit production in the study area. The major constraints to rabbit production were disease incidence (95%), poor access to credit facilities (90%), inadequate veterinary services (80%), high cost of feed (75%) and poor pricing of rabbit at the point of sale (60%). It is therefore recommended that seminars/workshops should be organised by the stakeholders to boost the knowledge and expertise of the rabbit farmers since education was a major determinant of income from rabbit production in the Study area.